2013
DOI: 10.1039/c2ta01325h
|View full text |Cite
|
Sign up to set email alerts
|

High-performance aqueous asymmetric electrochemical capacitors based on graphene oxide/cobalt(ii)-tetrapyrazinoporphyrazine hybrids

Abstract: A novel asymmetric electrochemical capacitor (AEC) with high energy and power densities has been developed using a graphene oxide/cobalt(II)tetrapyrazinoporphyrazine composite (GO/CoTPyzPz) as the positive electrode and graphene oxide/carbon black (GO/CB) as the negative electrode in a neutral aqueous Na 2 SO 4 electrolyte. The excellent specific capacitance, energy and power densities ($500 F g

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 25 publications
(31 reference statements)
0
18
0
Order By: Relevance
“…This we attribute to the uniform pore distribution which functions as a series of channels and may promote ion intercalation into these pores, creating more nano-pores after many CD cycle leading to increase in the efficiency. The initial decay may be related to the loss of adhesion between some of the active materials with the current collector during the continuous cycling process [40]. The specific capacitance and energy density are plotted as a function of current density and are shown in Figure 5 (e).…”
mentioning
confidence: 99%
“…This we attribute to the uniform pore distribution which functions as a series of channels and may promote ion intercalation into these pores, creating more nano-pores after many CD cycle leading to increase in the efficiency. The initial decay may be related to the loss of adhesion between some of the active materials with the current collector during the continuous cycling process [40]. The specific capacitance and energy density are plotted as a function of current density and are shown in Figure 5 (e).…”
mentioning
confidence: 99%
“…3a) are fairly rectangular showing the double layer capacitive behavior of all the presented CNFs inline with [22] however, the round edges and lifted corners at the extreme voltage show small faradaic reaction unlike redox dominant system where the CV curve shows many peaks [23]. The typical values of capacitance and specific capacitance calculated from the voltammogram for each sample is given in Table 1.…”
Section: Resultsmentioning
confidence: 98%
“…Among different existing nanomaterials used for miRNA detection, graphene oxide (GO) can be functionalized as an ideal transducing element thanks to high water dispersibility, stable affinity toward hydrophobic and/or pconjugated biomolecules, and the capability of uorescence quenching. [22][23][24] Former studies showed that GO could bind and quench dye-labeled single-stranded DNA (ssDNA) probes, while it had less binding affinity toward dsDNA or hybrids of DNA/ RNA. 25,26 Helicases are enzymes conserved from bacteria to humans that use ATP-driven motor force to unwind double-stranded DNA or RNA.…”
Section: Introductionmentioning
confidence: 99%